Rapid Fabrication of Sterile Medical Nasopharyngeal Swabs by Stereolithography for Widespread Testing in a Pandemic. Issue 11 (24th November 2020) - van der Elst, Louis A.; Gokce Kurtoglu, Merve; Leffel, Troy; Zheng, Mengxin; Gumennik, Alexander
Abstract : A plate of nasopharyngeal swabs propped upright for UV curing after having been printed by stereolithography in autoclavable, biocompatible dental resin. This setup shows 271 swabs with various head and shaft designs created to optimize the extraction of potential COVID‐19 specimen from patients for viral diagnostics. The design of the swabs follows strict requirements of durability, comfort, dimensions, and more, in accordance with CDC regulations, for widespread testing in a pandemic. Further details can found in the article, number 2000759, by Alexander Gumennik and co‐workers.